The Briny South : Displacement and Sentiment in the Indian Ocean World - Boer, Nienke, 1984- (Book collections on Project MUSE., 2023)
"The Briny South examines the legal, autobiographical, and fictional accounts by and about three groups of involuntary or coerced Indian Ocean migrants: enslaved persons transported to the Cape of Good Hope by the Dutch East India Company from their Indian Ocean outposts in South and Southeast Asia and East Africa in the seventeenth and eighteenth centuries; South Asian indentured laborers sent to the British colony of Natal between 1860 and 1911; and South African war prisoners shipped to camps in British India and Ceylon during the second South African War (1899-1902). Examining court records, ledgers, pamphlets, censors' reports, newsletters, folk songs, as well as South African and South Asian works of fiction and autobiography such as Mohandas K. Gandhi's Autobiography, Ansuyah R. Singh's novel, Behold the Earth Mourns, Thomas Pringle's poetry, and memoirs by Boer war prisoners, Nienke Boer focuses on sentiment, or the depiction of emotion, as a locus to understand how racialized identities are constructed through displacement in the imperial world"--